High-hardness, high-temperature-resistant and stain-resistant white ceramic microcrystalline glass and preparation method thereof

By spraying high-temperature resistant coating and oleophobic nanocoat after high-sonic wave and plasma equipment, the problem of white ceramic crystal crystal glass easily absorbing water, oil and scratches in the kitchen is solved, and high hardness, high temperature and stain resistance are achieved. Surface performance improves user experience and aesthetics.

CN119285252APending Publication Date: 2025-01-10DONGGUAN YINTAIFENG OPTICAL TECH CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411354044.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-26
Publication Date
2025-01-10

AI Technical Summary

Technical Problem

Existing white ceramic crystal glass is easy to absorb water and oil in kitchen appliances, surface dirt is difficult to clean, and scratches are easily caused by friction with stainless steel, affecting the beauty and user experience.

Method used

The surface of white ceramic microcrystalline glass is cleaned by high-sonic wave and plasma equipment. The high-temperature resistant coating water is sprayed to fill the micro gaps of the sponge structure and cure it at high temperature. Then the medium-temperature oleophobic nanocoating is sprayed to form an easy-to-clean layer to improve the Surface hardness and anti-fouling properties.

Benefits of technology

A layer of stain-resistant coating with high hardness, hydrophobic, oleophobic and high temperature resistance is formed. The surface is clear and smooth, and can resist long-term metal friction, which significantly improves stain-resistant performance and user experience.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119285252A_ABST
    Figure CN119285252A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of high-hardness, high-temperature-resistant and stain-resistant white ceramic microcrystalline glass. The preparation method comprises the following steps: S1, carrying out surface cleaning treatment on white ceramic microcrystalline glass by adopting high sound waves; s2, performing plasma cleaning treatment on the surface of the white ceramic microcrystalline glass subjected to the step S1 by adopting plasma equipment, and activating the surface activity of the white ceramic microcrystalline glass; s3, spraying a high-temperature-resistant coating liquid medicine on the white ceramic microcrystalline glass to enable the liquid medicine to fill micro gaps of a sponge structure of the white ceramic microcrystalline glass, then performing first baking, performing air cooling to normal temperature after the first baking is completed, and finally performing high-temperature curing to obtain the high-temperature-resistant white ceramic microcrystalline glass. And S4, secondary spraying is conducted on the surface of the primary treatment part through medium-temperature-resistant oleophobic nano coating liquid medicine, so that the surface of the primary treatment part is covered with the medium-temperature-resistant oleophobic nano coating liquid medicine, then third-time baking is conducted, an easy-to-clean layer can be formed after the primary treatment part is cooled to the normal temperature, and the white ceramic microcrystalline glass is obtained. The high-temperature-resistant and yellowing-resistant performance can be kept for a long time and cannot be changed in a short time.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of microcrystalline glass, and in particular to a high-hardness, high-temperature, and stain-resistant white ceramic microcrystalline glass and a preparation method thereof. Background Art

[0002] Glass-ceramics, also known as glass ceramics or microcrystalline ceramics, is a polycrystalline solid phase material containing glass obtained by controlled nucleation and crystallization of certain basic glasses of specific composition at a certain temperature. Glass-ceramics has the characteristics of both glass and ceramics, and is superior to metals and polymers in thermal, chemical, biological, optical and electrical properties, and is widely used in kitchen appliances.

[0003] like Figure 1 and Figure 2 White ceramic glass-ceramics are different from black and transparent glass-ceramics. Black and transparent glass-ceramics tend to be glass phase, while white glass-ceramics tend to be ceramic phase. The overall structure of white ceramic glass-ceramics is like a sponge at the microscopic level. There is a sponge-like structure inside the structure. This sponge structure is very easy to absorb water and oil in kitchen appliance applications. Once dirt remains in the structure, there is no way to clean it. During use, it is easy to scratch when rubbed against stainless steel pots. The dirt and scratches on the surface seriously affect the appearance and cannot meet the customer's visual and usage requirements. Summary of the invention

[0004] The purpose of the present invention is to overcome the above-mentioned defects in the prior art and provide a method for preparing white ceramic microcrystalline glass with high hardness, high temperature resistance and stain resistance. A layer of high hardness, hydrophobic, oleophobic, high temperature resistance and stain resistance coating can be formed on the surface of the white ceramic microcrystalline glass, and the high temperature resistance and yellowing resistance can be maintained for a long time and will not change in a short time.

[0005] To achieve the above object, the present invention provides a method for preparing high-hardness, high-temperature-resistant and stain-resistant white ceramic glass-ceramics, which is characterized by comprising the following steps:

[0006] Step S1: using high-frequency sound waves to clean the surface of white ceramic glass-ceramics;

[0007] Step S2: Then, a plasma device is used to perform plasma cleaning on the surface of the white ceramic glass-ceramic obtained in step S1 to activate its surface activity;

[0008] Step S3: spray the white ceramic glass-ceramics with a high temperature resistant coating solution to fill the micro gaps of the sponge structure of the white ceramic glass-ceramics with the solution, then perform the first baking, air cool to room temperature after completion, and finally perform high temperature curing to obtain a pre-treated part with a filling coating.

[0009] Wherein, the high temperature curing temperature is 700-780°C, and the high temperature resistant coating solution comprises 90%-95% polysilane polymer and 5%-10% crosslinking agent by mass percentage;

[0010] Step S4: spray the surface of the primary treatment piece with a medium-temperature resistant oleophobic nano coating solution for a second time to cover the surface of the primary treatment piece, and then bake it for a third time, and cool it to room temperature to form an easy-to-clean layer to obtain a white ceramic glass-ceramic;

[0011] The above-mentioned medium-temperature resistant oleophobic nano coating solution comprises, by mass percentage, 97% to 99% perfluoropolyether, 0.5% to 2% fluorosilane and 0.5 to 1% nano-scale filler.

[0012] Furthermore, in step S2, the plasma cleaning process uses a total of four plasma nozzles, each of which has a power of 700-800 W, a running speed of 1.3-1.6 m / min, a left-right swing speed of 5-10 m / min, and an interpolation speed of 0.5-2 m / min.

[0013] Furthermore, in step S3, the high temperature resistant coating solution is sprayed by two nozzles simultaneously, the flow rate of each nozzle is 30 g / min, the swing speed is 1.2-1.5 m / s, and the running speed is 1.3-1.6 m / min.

[0014] Furthermore, the temperature of the first baking is 200-220° C., and the baking time is 27-33 minutes; the temperature of the high-temperature baking is 740° C., and the baking time is 8-10 minutes.

[0015] Furthermore, the spraying amount of the high-temperature nano-layer solution is 60 g / m2.

[0016] Furthermore, the polysilane polymer is phenylsiloxane, and the cross-linking agent is triethoxysilane.

[0017] Furthermore, in step S3, the surface hardness of the obtained filling coating after curing is ≥7H.

[0018] Furthermore, in step S4, two nozzles are used for the medium-temperature resistant oleophobic nano-coating solution, each nozzle has a flow rate of 15 to 20 g / min, a swing speed of 1.2 to 1.5 m / s, a differential speed of 0.5 to 2 m / min, and a running speed of 1.3 to 1.6 m / min.

[0019] Furthermore, the filler comprises, by mass percentage relative to the high temperature resistant coating solution, 0.2-0.5% silicone resin, 0.2-0.3% silane and 0.1-0.2% siloxane.

[0020] A high-hardness, high-temperature-resistant and stain-resistant white ceramic microcrystalline glass is prepared by the above-mentioned high-hardness, high-temperature-resistant and stain-resistant white ceramic microcrystalline glass preparation method.

[0021] Compared with the prior art, the present invention has the following advantages:

[0022] 1. The surface of the white ceramic microcrystalline glass after spray coating of the present invention forms a layer of high hardness, hydrophobic, oleophobic, high temperature and stain resistant coating, and the high temperature and yellowing resistance can be maintained for a long time and will not change in a short time; the surface of the coating after spraying has a clear gloss, a smooth feel and strong stain resistance, a surface hardness ≥ 7H, and can resist long-term friction with metals such as stainless steel.

[0023] 2 The present invention adopts production line operation, robot and program automation operation, stable equipment and process parameters, and stable quality. BRIEF DESCRIPTION OF THE DRAWINGS

[0024] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0025] Figure 1 It is a microscopic enlarged schematic diagram of white ceramic glass-ceramic;

[0026] Figure 2 It is a microscopic magnified schematic diagram of black and transparent glass-ceramics;

[0027] Figure 3 It is a schematic diagram of the effect of the wiping test;

[0028] Figure 4 It is a schematic diagram of the effect of comparative wiping test;

[0029] Figure 5 It is a schematic diagram of the pollution resistance boiling water test;

[0030] Figure 6 This is a comparative diagram of the pollution resistance boiling water test;

[0031] Figure 7 This is a schematic diagram of the effect of the pollution resistance boiling water test;

[0032] Figure 8 It is a schematic diagram of the process of the present invention. DETAILED DESCRIPTION

[0033] The technical scheme in this embodiment of the present invention will be clearly and completely described below in conjunction with the drawings in this embodiment of the present invention. Obviously, the described embodiment is one embodiment of the present invention, not all embodiments of the present invention. Based on this embodiment of the present invention, all other embodiments of the present invention obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] It should be noted that all directional indications in the embodiments of the present invention (such as up, down, left, right, front, back, etc.) are only used to explain the relative position relationship, movement status, etc. between the components under a certain specific posture (as described in the accompanying drawings). If the specific posture changes, the directional indication will also change accordingly.

[0035] In addition, if there are descriptions involving "first", "second", etc. in the embodiments of the present invention, the descriptions of "first", "second", etc. are only used for descriptive purposes and cannot be understood as indicating or implying their relative importance or implicitly indicating the number of the indicated technical features.

[0036] The embodiment of the present invention provides a white ceramic glass-ceramic high-hardness, high-temperature, and stain-resistant coating processing technology, which is as follows:

[0037] The present invention provides a method for preparing high-hardness, high-temperature-resistant and stain-resistant white ceramic glass-ceramics. Figure 8 As shown, the following steps are included:

[0038] Step S1: using high-frequency sound waves to clean the surface of white ceramic glass-ceramics;

[0039] Step S2: Then, a plasma device is used to perform plasma cleaning on the surface of the white ceramic glass-ceramic obtained in step S1 to activate its surface activity;

[0040] Step S3: spraying the white ceramic glass-ceramic with a high temperature resistant coating solution, mainly to prime the surface of the white ceramic glass-ceramic so that the solution fills the micro gaps in the sponge structure of the white ceramic glass-ceramic, making the structure denser, harder, and less likely to be penetrated by dirt, and then performing the first baking, after which the solution is air-cooled to room temperature, and finally performing high temperature curing to obtain a pre-treated part with a filling coating.

[0041] Wherein, the high temperature curing temperature is 700-780°C, and the high temperature resistant coating solution comprises 90%-95% polysilane polymer and 5%-10% crosslinking agent by mass percentage;

[0042] Step S4: Use a medium-temperature resistant oleophobic nano-coating solution to spray the surface of the initially treated part for a second time to cover the surface of the initially treated part, and then bake it for a third time. After cooling to room temperature, an easy-to-clean layer can be formed to obtain white ceramic microcrystalline glass; using a medium-temperature resistant oleophobic nano-coating solution to spray on the high-temperature resistant coating structure formed by the high-temperature resistant coating solution can increase the pollution resistance level, improve the oleophobic effect and surface smoothness, and improve the user experience.

[0043] The above-mentioned medium-temperature resistant oleophobic nano coating solution comprises, by mass percentage, 97% to 99% perfluoropolyether, 0.5% to 2% fluorosilane and 0.5 to 1% nano-scale filler.

[0044] Furthermore, in step S2, the plasma cleaning process uses a total of four plasma nozzles, each of which has a power of 700-800 W, a running speed of 1.3-1.6 m / min, a left-right swing speed of 5-10 m / min, and an interpolation speed of 0.5-2 m / min.

[0045] Furthermore, in step S3, the high temperature resistant coating solution is sprayed by two nozzles simultaneously, the flow rate of each nozzle is 30 g / min, the swing speed is 1.2-1.5 m / s, and the running speed is 1.3-1.6 m / min.

[0046] Furthermore, the temperature of the first baking is 200-220° C., and the baking time is 27-33 minutes; the temperature of the high-temperature baking is 740±40° C., and the baking time is 8-10 minutes.

[0047] Furthermore, the spraying amount of the high-temperature nano-layer solution is 60 g / m2.

[0048] Furthermore, the polysilane polymer is phenylsiloxane, and the cross-linking agent is triethoxysilane.

[0049] Furthermore, in step S3, the surface hardness of the obtained filling coating after curing is ≥7H.

[0050] Furthermore, in step S4, two nozzles are used for the medium-temperature resistant oleophobic nano-coating solution, each nozzle has a flow rate of 15 to 20 g / min, a swing speed of 1.2 to 1.5 m / s, a differential speed of 0.5 to 2 m / min, and a running speed of 1.3 to 1.6 m / min.

[0051] Furthermore, the filler includes 0.2-0.5% silicone resin, 0.2-0.3% silane and 0.1-0.2% siloxane by mass percentage. The filler is an additional filler on the basis of the high temperature resistant coating solution 740 baking, so that the surface coating is denser, and oil stains are not easy to penetrate into the interior of the ceramic glass, playing a second anti-fouling role.

[0052] A high-hardness, high-temperature-resistant and stain-resistant white ceramic microcrystalline glass is prepared by the above-mentioned high-hardness, high-temperature-resistant and stain-resistant white ceramic microcrystalline glass preparation method.

[0053] Example 1

[0054] The method for preparing the high-hardness, high-temperature-resistant and stain-resistant white ceramic glass-ceramics of this embodiment comprises the following steps:

[0055] Step S1: using high-frequency sound waves to clean the surface of white ceramic glass-ceramics;

[0056] Step S2: Then, a plasma device is used to perform plasma cleaning on the surface of the white ceramic glass-ceramic that has completed step S1 to activate its surface activity. Specifically, during the treatment, the plasma cleaning device uses a total of four plasma nozzles, each of which has a power of 700 to 800 W, a running speed of 1.3 to 1.6 m / min, a left and right swing speed of 5 to 10 m / min, and an interpolation speed of 0.5 to 2 m / min;

[0057] Step S3: spray the white ceramic microcrystalline glass with a high temperature resistant coating solution to fill the micro gaps of the sponge structure of the white ceramic microcrystalline glass with the solution. The specific spraying method is to use an automated spraying device with two nozzles to operate simultaneously, and the flow rate of each nozzle is 30 grams / minute, so that the spraying amount of the high temperature nanolayer solution is 60±5 grams / square meter, the swing speed is 1.2 to 1.5 meters / second, and the running speed is 1.3 to 1.6 meters / minute. Spraying is performed. It should be noted that the spraying amount has an effect on the density of the coating. If it is less than 55 grams / square meter, the density is insufficient, which affects the anti-fouling effect, and if it is higher than 65 grams / square meter, the cost will increase; then the first baking is performed, the temperature of the first baking is 200°C, and the baking time is set to 9 minutes after completion. The high temperature curing is finally performed at 740°C. The present embodiment uses a physical tempering furnace for high temperature curing. The set baking temperature of the physical tempering furnace is 740°C, and the baking time is set to 9 minutes. The specific parameter settings are as follows:

[0058] Heating time: 540±20s; furnace exit speed: 465±15mm / s; furnace temperature setting: zone 1: 710±10℃, zone 2: 720±10℃, zone 3: 730±10℃, zone 4: 740±10℃; upper and lower wind distance: 4±1mm for quenching, 4±0.5mm for cooling; upper and lower quenching wind pressure: 3±1kPa, upper and lower cooling wind pressure: 1.85±0.6kPa. After curing, the initial treated parts with filling coating are obtained;

[0059] In this embodiment, the high temperature resistant coating solution comprises 90% polysilane polymer and 10% cross-linking agent by mass percentage;

[0060] Step S4: Use medium-temperature resistant oleophobic nano-coating solution to spray the surface of the primary treatment part for a second time to cover the surface of the primary treatment part. In this embodiment, the secondary spraying also uses automatic spraying equipment, using two nozzles, and the flow rate of each nozzle is 15 g / min. Of course, it can be adjusted according to actual conditions and controlled between 15 and 20 g / min. The swing speed is 1.2 to 1.5 m / s, the differential speed is 0.5 to 2 m / min, and the running speed is 1.3 to 1.6 m / min. Similarly, when the spraying amount is less than 15 g / min, the density of the coating is insufficient, which affects the anti-fouling effect, and when it is higher than 20 g / min, the cost increases; after completing the secondary spraying, continue to bake for the third time, the baking temperature is 150°C, the baking time is 30 minutes, and the easy-to-clean layer can be formed when it is cooled to room temperature to obtain white ceramic microcrystalline glass;

[0061] The above-mentioned medium-temperature resistant oleophobic nano coating solution comprises, by mass percentage, 97% perfluoropolyether, 2% fluorosilane and 1% nano-scale filler.

[0062] The polysilane polymer is phenylsiloxane, and the cross-linking agent is triethoxysilane;

[0063] Preferably, in step S3, the surface hardness of the obtained filling coating after curing is ≥7H 。

[0064] The present invention firstly uses ultrasonic equipment to perform a first physical polishing on the surface of the white ceramic microcrystalline glass to reduce the burrs on its surface, then uses plasma equipment to perform a secondary chemical polishing to activate the surface activity of the white ceramic microcrystalline glass, and then sprays the surface of the white ceramic microcrystalline glass with a high temperature resistant coating solution, so that the high temperature resistant coating solution can fill the micro gaps of the sponge structure of the white ceramic microcrystalline glass, so that the solution fills the micro gaps, and then performs a first baking to harden the high temperature resistant coating solution, and then air cools to room temperature, and then performs high temperature curing at a high temperature of 740°C, so that the high temperature resistant coating solution completely covers the sponge structure to form an ultra-high temperature resistant high hardness coating with a hardness greater than 7H, and then sprays a medium temperature resistant nano coating solution on the basis of the ultra-high temperature resistant high hardness coating to fill the gaps between the ultra-high temperature resistant high hardness coatings, thereby making the surface of the white ceramic microcrystalline glass denser, and oil stains are not easy to penetrate into the interior of the ceramic glass, thereby playing a second anti-fouling role.

[0065] Product performance test:

[0066] (1) Glossiness, roughness test, LAB color difference comparison and water drop angle test

[0067] The white ceramic glass-ceramics prepared by the above method were tested by gloss meter, surface roughness tester, colorimeter and water drop angle tester in turn to obtain the data in Table (1).

[0068]

[0069] Table 1

[0070] The standards for this round of testing are: gloss test results between 15-25, roughness test results less than 2.5, and water drop angle greater than 110 degrees, which is qualified.

[0071] As can be seen from Table (1), the product obtained from Example 1 was subjected to 9 glossiness, roughness and LAB color difference comparison tests; and three water drop angle tests. It can be seen from the table that the average values ​​of the test results are all within the qualified requirement range, and the test structure is qualified.

[0072] (2) Wipe test

[0073] The white ceramic glass-ceramics prepared in Example 1 and the white ceramic glass-ceramics without coating were used for comparative testing. Four oil-based pens were used to paint on the surfaces of the two glass-ceramics, respectively. The four oil-based pens were whiteboard pens, marker pens, snowman paint pens, and uniPX-21 paint pens. After painting, a magic sponge of the same material was used to dry wipe. Figure 3 The white ceramic glass-ceramic prepared by this embodiment 1 can be wiped clean. Figure 4 As shown, uncoated white ceramic glass-ceramic cannot erase the marks of oil-based markers.

[0074] (3) Boiling water resistance test

[0075] like Figure 5-Figure 7 As shown, 150-250℃ / 1200H simulated usage scenario boiling water: simply install the white ceramic microcrystalline glass on the induction cooker assembly machine, apply "a mixture of kimchi water and cooking oil" on the glass 3-4 stove positions, press a stainless steel pot filled with water on the mixture, start the assembly machine to boil water (the water is kept in a boiling state), do a 1H-1H cycle test, wipe once every 100H, the cumulative boiling time is 1200H, use common kitchen detergents and brushes to clean, and the dirt can be wiped off as OK. The surface dirt with the high-hardness, high-temperature and stain-resistant coating process of white ceramic microcrystalline glass can be wiped off, and the result is OK.

[0076] Example 2

[0077] The difference between this embodiment and embodiment 1 is that the high temperature resistant coating solution in step S3 includes 93% polysilane polymer and 7% cross-linking agent by mass percentage; the others remain unchanged;

[0078] Example 3

[0079] The difference between this embodiment and embodiment 1 is that the high temperature resistant coating solution in step S3 includes 95% polysilane polymer and 5% cross-linking agent by mass percentage; the rest remain unchanged.

[0080] Example 4

[0081] The difference between this embodiment and embodiment 1 is that step S4 includes 98% perfluoropolyether, 1% fluorosilane and 1% nano-scale filler; the others remain unchanged.

[0082] Example 5

[0083] The difference between this embodiment and embodiment 1 is that step S4 includes 99% perfluoropolyether, 0.5% fluorosilane and 0.5% nano-scale filler; the others remain unchanged.

[0084] Example 6

[0085] The difference between this embodiment and embodiment 1 is that in step S3, the temperature of high temperature curing is 800° C.; the others remain unchanged.

[0086] Example 7

[0087] The difference between this embodiment and embodiment 1 is that in step S3, the temperature of high temperature curing is 700° C.; the others remain unchanged.

[0088] Comparative Example 1

[0089] The difference between this comparative example and Example 1 is that in step S3 of this example, the high temperature curing temperature is 180° C., the curing temperature is 30 minutes, and the other conditions remain unchanged.

[0090] Comparative Example 2

[0091] The difference between this comparative example and Example 1 is that step S3 is eliminated, and only the coating spraying of step S4 is performed, and the rest remain unchanged.

[0092] Comparative Example 3

[0093] The difference between this embodiment and embodiment 1 is that the high temperature resistant coating solution in step S3 includes 80% polysilane polymer and 20% cross-linking agent by mass percentage; the rest remain unchanged.

[0094] Comparative Example 4

[0095] The difference between this embodiment and embodiment 1 is that the high temperature resistant coating solution in step S3 includes 97% polysilane polymer and 3% cross-linking agent by mass percentage; the rest remain unchanged.

[0096] Comparative Example 5

[0097] The difference between this embodiment and embodiment 1 is that step S4 includes 90% perfluoropolyether, 5% fluorosilane and 5% nano-scale filler; the others remain unchanged.

[0098] Comparative Example 6

[0099] The difference between this embodiment and embodiment 1 is that step S4 includes 95% perfluoropolyether, 2.5% fluorosilane and 2.5% nano-scale filler; the others remain unchanged.

[0100] The high-hardness, high-temperature-resistant and stain-resistant white ceramic glass-ceramics obtained in Examples 1 to 6 and Comparative Examples 1 to 6 were subjected to a hardness test, and the finished products obtained in the above examples were subjected to a stain wiping test. The test results are shown in Table 2:

[0101] hardness Dry Rub Alcohol wipes Example 1 8H Slight traces after wiping No trace after wiping Example 2 8H Slight traces after wiping No trace after wiping Example 3 8H Slight traces after wiping No trace after wiping Example 4 8H Slight traces after wiping Slight traces after wiping Example 5 8H Slight traces after wiping Slight traces after wiping Example 6 8H Slight traces after wiping Slight traces after wiping Example 7 8H Slight traces after wiping Slight traces after wiping Comparative Example 1 8H Slight traces after wiping Slight traces after wiping Comparative Example 2 6H Obvious traces after wiping Obvious traces after wiping Comparative Example 3 7H Slight traces after wiping Slight traces after wiping Comparative Example 4 8H Slight traces after wiping Slight traces after wiping Comparative Example 5 8H Slight traces after wiping Slight traces after wiping Comparative Example 6 8H Slight traces after wiping Slight traces after wiping

[0102] Table 2

[0103] From Table 2, by comparing Examples 1 to 3 and Comparative Examples 3 and 4, it can be seen that, under the same curing temperature and time, the increase in the polysilane polymer content has no effect on the hardness, but has an effect on the stain resistance effect.

[0104] By comparing Example 1 with Examples 4-5 and 5 with 6, it can be seen that, under the condition that other conditions remain unchanged, perfluoropolyether / fluorosilane / filler has an impact on the antifouling effect, and the ratio exceeding the standard range has an impact on the density of the surface coating and the antifouling effect.

[0105] By comparing Example 1, Example 6, Example 7 and Comparative Example 1, it can be seen that, when other conditions remain unchanged, changing the temperature of high-temperature curing in step S3 has a significant effect on the hardness of the finished product. As the temperature changes, it has no effect on the hardness, but has an effect on the anti-fouling effect.

[0106] By comparing Examples 1-7 and Comparative Example 2, it can be seen that, under the condition that other conditions remain unchanged, the coating formed after the high-temperature resistant coating solution is cured has a significant effect on the hardness of the finished product. Adding step S3 significantly increases the hardness and improves the anti-fouling effect.

[0107] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.

Claims

1. A method for preparing high-hardness, high-temperature-resistant and stain-resistant white ceramic glass-ceramics, characterized in that: The steps include: Step S1: using high-frequency sound waves to clean the surface of white ceramic glass-ceramics; Step S2: Then, a plasma device is used to perform plasma cleaning on the surface of the white ceramic glass-ceramic that has completed step S1, so as to activate its surface activity; Step S3: spray the white ceramic glass-ceramics with a high temperature resistant coating solution to fill the micro gaps of the sponge structure of the white ceramic glass-ceramics with the solution, then perform the first baking, air cool to room temperature after completion, and finally perform high temperature curing to obtain a pre-treated part with a filling coating. Wherein, the high temperature curing temperature is 700-780°C, and the high temperature resistant coating solution comprises 90%-95% polysilane polymer and 5%-10% crosslinking agent by mass percentage; Step S4: spray the surface of the primary treatment piece with a medium-temperature resistant oleophobic nano coating solution for a second time to cover the surface of the primary treatment piece, and then bake it for a third time, and cool it to room temperature to form an easy-to-clean layer to obtain a white ceramic glass-ceramic; The above-mentioned medium-temperature resistant oleophobic nano coating solution comprises, by mass percentage, 97% to 99% perfluoropolyether, 0.5% to 2% fluorosilane and 0.5 to 1% nano-scale filler.

2. The method for preparing the high-hardness, high-temperature-resistant and stain-resistant white ceramic glass-ceramics according to claim 1, characterized in that: In step S2, the plasma cleaning process uses a total of four plasma nozzles, each of which has a power of 700-800W, a running speed of 1.3-1.6 m / min, a left-right swing speed of 5-10 m / min, and an interpolation speed of 0.5-2 m / min.

3. The method for preparing the high-hardness, high-temperature-resistant and stain-resistant white ceramic glass-ceramics according to claim 1, characterized in that: In step S3, the high temperature resistant coating solution is sprayed by two nozzles at the same time, the flow rate of each nozzle is 30 g / min, the swing speed is 1.2-1.5 m / s, and the running speed is 1.3-1.6 m / min.

4. The method for preparing the high-hardness, high-temperature-resistant and stain-resistant white ceramic glass-ceramics according to claim 3, characterized in that: The temperature of the first baking is 200-220° C., and the baking time is 27-33 minutes; the temperature of the high-temperature baking is 740° C., and the baking time is 8-10 minutes.

5. The method for preparing the high-hardness, high-temperature-resistant and stain-resistant white ceramic glass-ceramics according to claim 3, characterized in that: The spraying amount of the high-temperature nano-layer solution is 60 g / m2.

6. The method for preparing the high-hardness, high-temperature-resistant and stain-resistant white ceramic glass-ceramics according to claim 5, characterized in that: The polysilane polymer is phenylsiloxane, and the cross-linking agent is triethoxysilane.

7. The method for preparing high-hardness, high-temperature-resistant and stain-resistant white ceramic glass-ceramics according to claim 1, characterized in that: In step S3, the surface hardness of the obtained filling coating after curing is ≥7H.

8. The method for preparing the high-hardness, high-temperature-resistant and stain-resistant white ceramic glass-ceramics according to claim 1, characterized in that: In step S4, two nozzles are used for the medium-temperature resistant oleophobic nano coating solution, each nozzle has a flow rate of 15 to 20 g / min, a swing speed of 1.2 to 1.5 m / s, a differential speed of 0.5 to 2 m / min, and a running speed of 1.3 to 1.6 m / min.

9. The method for preparing high-hardness, high-temperature-resistant and stain-resistant white ceramic glass-ceramics according to claim 1, characterized in that: The filler comprises, by mass percentage relative to the high temperature resistant coating solution, 0.2-0.5% of organic silicon resin, 0.2-0.3% of silane and 0.1-0.2% of siloxane.

10. A high-hardness, high-temperature-resistant and stain-resistant white ceramic glass-ceramic, characterized in that: The white ceramic glass-ceramics is prepared by the preparation method of the high-hardness, high-temperature-resistant and stain-resistant white ceramic glass-ceramics according to claims 1-9.